Predictive Modeling of Rice Production in South America Using Machine Learning - Grion, Renan; Koifman, Ana Bari; Moraes, Laura O.; Ferreira, Mariana Simoes Larraz (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2026)
Research Context: Rice is a staple food for nearly half of the global population and is highly vulnerable to climate variability. In South America, accurate forecasting models are critical to ensure food security and guide agricultural decision-making. Scientific and/or Practical Problem: Traditional methods often fail to capture the complexity of agricultural systems shaped by environmental and socioeconomic factors. The lack of predictive systems adapted to South America restricts the ability of governments and producers to anticipate risks. This research addresses both a scientific challenge, by advancing predictive modeling, and a practical challenge, by supporting sustainable agricultural planning. Proposed Solution and/or Analysis: The study integrates agricultural production data from FAOSTAT (2004–2023) with climate variables from NASA POWER (2011–2023). It compares Linear Regression, Support Vector Regression (SVR), and XGBoost Regressor to identify the most reliable configuration for rice production forecasting. Related IS Theory: The work aligns with decision support systems (DSS) and information systems for sustainability, contributing to the Brazilian Grand Challenges in Information Systems (GranDSI-BR 2016–2026). Research Method: The approach combined exploratory analysis, training with multiple time windows (5, 10, 15 years), and cross-validation, using Mean Absolute Percentage Error (MAPE) as the main evaluation metric. Summary of Results: Longer windows (10 years) improved stability. XGBoost achieved the lowest MAPE and greater robustness, while climate data integration reduced errors in atypical years. Contributions and Impact to IS area: The study demonstrates the potential of machine learning–based predictive systems as components of agricultural information systems, reinforcing their role in enhancing food security, supporting public policies, and promoting sustainable resource management in South America and beyond.